CAPILLARY ION CHROMATOGRAPHY WITH CONTACTLESS CONDUCTIVITY DETECTION FOR THE SEPARATION OF INORGANIC CATIONS USING POLYMER MONOLITHIC COLUMN - Toyohide Takeuchi, Femi Earnestly, Lee Wah Lim (Menara Ilmu, 2017)
Since two decades ago, the innovations of many gifted analysts have brought us to a new era phase in chromatography, i.e., monolithic materials, both silica- or polymer-based. These materials have high permeability, no need to frits preparation and fast mass transfer. In this research, polymer monolithic columns were used for separation of inorganic cations by using contactless conductivity detector. Glycidyl methacrylate (GMA) and polyethylene glycol dimethacrylate (PEGDMA) were used as monomer and crosslinker. Methanol and decanol were used as binary porogenic solvents. The monolith columns were prepared by two-step procedures: polymerization and sulfonation of GMA. This polymer monolitic column could separate lithium, sodium and rubidium with the5mMMSA in 50% methanol as eluent.     Keywords: polymer monolithic column, contacless conductivity detector,separation of inorganic cations